Biochemical characteristics of fresh and freeze/thawed seminal plasma of alpaca (Vicugna pacos) - Díaz V., Hugo (2015)
The aim of this study was to determine and compare the biochemical characteristics of fresh and thawed seminal plasma of alpacas. Semen was collected by electroejaculation from four adult males, once a week per four weeks. Semen was centrifuged and the seminal plasma was separated. One part was analysed fresh and other stored for one month on liquid nitrogen and then thawed and analysed. Levels of glucose, total cholesterol, HDL-cholesterol, triglycerides, total protein, albumin, calcium, alkaline phosphatase, ALT and -GT were determined. Only the triglycerides significantly decreased due to the process of freeze/thawed, where the values were 44.12 ± 7.38 and 27.31 ± 4.65 mg/dl in fresh and thawed respectively